Nifurpirinol: A more potent and reliable substrate compared to metronidazole for nitroreductase‐mediated cell ablations. Issue 2 (19th May 2018) - Bergemann, David; Massoz, Laura; Bourdouxhe, Jordane; Carril Pardo, Claudio A.; Voz, Marianne L.; Peers, Bernard; Manfroid, Isabelle
Abstract: The zebrafish is a popular animal model with well‐known regenerative capabilities. To study regeneration in this fish, the nitroreductase/metronidazole‐mediated system is widely used for targeted ablation of various cell types. Nevertheless, we highlight here some variability in ablation efficiencies with the metronidazole prodrug that led us to search for a more efficient and reliable compound. Herein, we present nifurpirinol, another nitroaromatic antibiotic, as a more potent prodrug compared to metronidazole to trigger cell‐ablation in nitroreductase expressing transgenic models. We show that nifurpirinol induces robust and reliable ablations at concentrations 2, 000 fold lower than metronidazole and three times below its own toxic concentration. We confirmed the efficiency of nifurpirinol in triggering massive ablation of three different cell types: the pancreatic beta cells, osteoblasts, and dopaminergic neurons. Our results identify nifurpirinol as a very potent prodrug for the nitroreductase‐mediated ablation system and suggest that its use could be extended to many other cell types, especially if difficult to ablate, or when combined pharmacological treatments are desired.